The review (typology) of small and medium-sized business in Russia and abroad - K. V. Glukhov; D. A. Smolina (Вестник университета)
The article examines the problem of classification of small and medium-sized business in Russia, which is relevant due to the increase in state support for them, in order to increase the targeting of the support provided. The article also discusses the development of small and medium-sized business in Russia since the end of the previous century, its gradually changing legislative regulation and comparison of criteria for classification of small and medium-sized business in Russia and foreign countries. In addition, the question is raised about small and medium-sized business falling out of the official classification, while, by their nature of activity, do not cease to be such and possible causes of this phenomenon. In order to resolve controversial issues of classification, some assumptions and possible ways to solve are put forward in the article on the basis of the conducted research that can eliminate gaps in legislation. Within the framework of writing this article, such scientific research methods were used as analysis and generalization of domestic and foreign anti-crisis measures.